Gravitational higher-form symmetries and the origin of hidden symmetries in Kaluza-Klein compactifications - Carmen Gómez-Fayrén, Tomás Ortín, Matteo Zatti (SciPost Physics Core)
We show that, in presence of isometries and non-trivial topology, the Einstein–Hilbert action is invariant under certain transformations of the metric which are not diffeomorphisms. These transformations are similar to the higher-form symmetries of field theories with $p$-form fields. In the context of toroidal Kaluza–Klein compactifications, we show that these symmetries give rise to some of the "hidden symmetries" (dualities) of the dimensionally-reduced theories.